AKUMULASI TIMBAL (Pb ) PADA TALUS LICHENES DI KOTA PEKAN BARU - Nursal '; Firdaus '; basori ' (Program Studi Pendidikan Biologi, 2005)
The research accumulation of Leads in Lichens thallus had carried out on March until June 2003. Samples o f Lichenes was taken from tree bark at three locations in Pekanbaru City , were; Sudirman and Soebrantas streets. The accumulation of Leads analyze with Atomic Absorbance Spectrophotometers - AAS . The results of this research that Lead contents in Lichenes that grow on tree bark on Pekanbaru City about 4,36 - 23,14 ppm. The correlation of relative humidity of air with Lead accumulation in Lichenes thallus had more higher than another factors . Key words : Leads, Lichenes, Pekanbaru city